2021
DOI: 10.1186/s12967-021-02716-6
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of chemotaxis and the complement system in the formation and progression of thoracic aortic aneurysms inferred from the weighted gene coexpression network analysis

Abstract: Background Thoracic aortic aneurysm (TAA) can be life-threatening due to the progressive weakening and dilatation of the aortic wall. Once the aortic wall has ruptured, no effective pharmaceutical therapies are available. However, studies on TAA at the gene expression level are limited. Our study aimed to identify the driver genes and critical pathways of TAA through gene coexpression networks. Methods We analyzed the genetic data of TAA patients f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…However, different cells of the immune system (ex. T cells, macrophages) have been observed in human TAA, and several relative inflammatory pathways are reported to be activated [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…However, different cells of the immune system (ex. T cells, macrophages) have been observed in human TAA, and several relative inflammatory pathways are reported to be activated [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that C3AR1 may be a hub between the regulation of inflammation and glucolipid metabolism. In addition, the expression of C3AR1 has been suggested to be associated with the formation of thoracic aortic aneurysms ( 43 ). A study by Propson et al found that mice with C3AR1 knockout in vascular endothelial cells had a significantly diminished tendency toward vascular aging with age, with abnormal activation of peripheral immune cells and reduced inward flow ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…This structure, known as a co-expression profile, allows for identification and clarification of gene relationships [ 8 ]. WGCNA has been previously used in an attempt to identify genes and pathways relevant to TAA development [ 9 ], but it has not been applied to find the gene expression differences between TAA/BAV and TAA/TAV patients. In this study, we intend to fill in this gap in knowledge by using WGCNA to elucidate those gene expression differences, as well as the underlying molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%